'Weird life' as wildlife consciousness in D.O Fagunwa's African literary imagination. Issue 2 (3rd April 2021) - Coker, Oluwole
ABSTRACT: D.O Fagunwa is a foremost and celebrated writer who wrote his major works in his indigenous Yoruba language. He published five major works: Ogboju Ode Ninu Igbo Irunmale (1938); Igbo Olodumare (1949); Ireke Onibudo (1949); Irinkerindo Ninu Igbo Elegbeje (1949); and Adiitu Eledumare (1961). These have all been translated into English hence Fagunwa's place in African literary pantheon is assured. Against this above backdrop, through a close reading of Igbo Olodumare (1949) translated Forest of Olodumare (2010) by Wole Soyinka, this paper connects 'weird life' narration as a corollary of wildlife consciousness in D.O Fagunwa. The essay is inspired by the submissions of Tola Badejo and draws insights from Ecocriticism and Magical Realism. This is activated through the novel's hunter protagonist. Fagunwa therefore locates indigenous wildlife consciousness within his weird settings and character portraitures. The paper affirms the enduring brilliance of Fagunwa's novelistic explorations by calling attention to how his novels serve as a template for wildlife conservation, animal ethics and biodiversity. The paper hopes to demonstrate how Fagunwa's enabling Yoruba context constructs animal imagery thereby foregrounding the place of wildlife consciousness in African literary imagination.